Assessment of damages under the convention on contracts for the International sale of goods (CISG) - Ali, Rahand Raouf (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2012)
In the international sale of goods, once a contract is breached, damages are one of the most common remedies that the injured party claims from the breaching party. The injured party would require the breaching party to remedy the damages resulting from the breach of contract. Therefore, the knowledge of the damage rules under the applicable law is crucial to the interests of the contracting parties. An effective damage rule should offer the contracting parties with a predictable outcome. In other words, it should be clear to the contracting parties about what damages are recoverable and when they are recoverable. The aim of this thesis is to explore the remedy of damages under the international convention on contracts in the international sales of goods (CISG). The United Nations Convention on Contracts for the International Sale of Goods (CISG) is one of the most successful international instruments that provide uniformity in the rules for international trade The issue addressed in this thesis include: the basis for the right to claim damages, the idea of limitation of damages, causation, foreseeability and mitigation, principle underlying the award of damages; classification of losses and how to recover damages. Also this thesis draws to how the interest will calculate. This thesis attempts to provide justification for the existing rule of damages, highlights the problems in their interpretation and application of provision, and proposes solutions to the existing problem in the light of relevant policies and goals pursued by the international instrument to fill the gap the is existing in the CISG. The problems associated with remedies under the Convention arise because the provisions concerning the payment of damages and interest set forth only very general rules. In such situations, the Convention states that, in interpreting the Convention, “regard is to be had to its international character and to the need to promote uniformity in its application and observance of good faith in international trade.” It further states: Questions concerning matters governed by this Convention which are not expressly settled in it are to be settled in conformity with the general principles on which it is based or, in the absence of such principles, in conformity with the law applicable by virtue of the rules of private international law. Despite these provisions, many courts and tribunals simply apply domestic rules to fill gaps in the Convention. This is especially true where it has been unclear whether the matter is governed by substantive law or procedural law.